2019
DOI: 10.34010/jati.v9i1.1410
|View full text |Cite
|
Sign up to set email alerts
|

PEMANFAATAN KAMERA DENGAN SENSOR APS-C PADA PENELUSURAN LAPANGAN KAWASAN RAWAN BENCANA UNTUK INFORMASI SPASIAL MITIGASI BENCANA SIGDa

Abstract: Data spasial yang diaplikasikan Bappeda Kabupaten Lombok Barat pada SIGDa memerlukan pembaruan data spasial tiap tahunnya. untuk mendukung penyusunan perencanaan program pembangunan dan program kerja Pemda Kabupaten Lombok Barat. Penyusunan perencanaan program pembangunan pemerintah juga memperhatikan adanya potensi bencana alam. Pemda Kabupaten Lombok Barat memerlukan upaya pembaruan data spasial secara tahunan, penyediaan yang cepat, efisien dan biaya yang murah. Perangkat foto udara sederhana merupakan alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The following graph illustrates the trend of natural disasters over the last 5 years. Disaster management is efforts and measures used to prevent, tame or mitigate, rescue, rehabilitate, and reconstruct disaster before, during, and after the occurrence (Pribadi and Meranti, 1996). Kusmiati (2005) showed that it is an institutionalized effort directed at preventing and minimizing losses as well as increasing community capacity Currently, the increased recognition of good governance serves as an enabling factor for disaster management because it promotes collaboration at all levels of authority.…”
Section: Introductionmentioning
confidence: 99%
“…The following graph illustrates the trend of natural disasters over the last 5 years. Disaster management is efforts and measures used to prevent, tame or mitigate, rescue, rehabilitate, and reconstruct disaster before, during, and after the occurrence (Pribadi and Meranti, 1996). Kusmiati (2005) showed that it is an institutionalized effort directed at preventing and minimizing losses as well as increasing community capacity Currently, the increased recognition of good governance serves as an enabling factor for disaster management because it promotes collaboration at all levels of authority.…”
Section: Introductionmentioning
confidence: 99%